Design and Production of Biofunctional PVA/PLA Double-Layered Fiber Wound Dressing by Electrospinning Method - Kose, Alpay; Altan, Eray; Abdulazez, Israa F.; Bingol, Ayse Betul; Yilmaz, Hilal; Erarslan, Azime; Gunduz, Oguzhan; Ustundag, Cem Bulent (WILEY, 2025)
In this study, a double-layered wound dressing combined with biofunctional components was produced, and characterization studies were conducted. To produce fiber wound dressing, polylactic acid (PLA) and polyvinyl alcohol (PVA) were used in the layers, and the electrospinning method was preferred. Propolis extract and aloe vera gel were preferred as biofunctional components and combined according to the degradability of the polymers and the intended use. The obtained wound dressing samples were subjected to antibacterial analyses, scanning electron microscopy (SEM), Fourier Transform-Infrared Spectroscopy (FT-IR) to analyze bond structures and detect the presence of added components, X-ray diffraction (XRD) to analyze the crystallinity of the components, swelling tests, tensile tests to evaluate the mechanical strength of each layer of the wound Dressing, and finally differential scanning calorimetry (DSC) characterization studies to observe the thermal changes with temperature. In this study, the bilayer fiber was found to be effective against S. aureus. The average fiber diameter was measured as 0.36 +/- 0.32 mu m, with strong peaks observed at 19.52, 19.90, and 37.83 nm. The bilayer fiber reached 198% saturation at the 5th hour, and its tensile strain was determined as 98.85% +/- 22.45%. As a result of the results obtained, this study not only demonstrates the suitability of using the double-layered fiber structure as a wound dressing but also sets an example for future studies on how different polymers and various biofunctional compounds and extracts found in nature can be combined into composite structures, thus producing structures with more desired properties.
Keywords: biofunctional compounds; electrospinning; PLA; PVA; wound dressing; ALOE-VERA; ALCOHOL; Polymer Science